The effect of intestinal microbiota on pregnancy and baby's health - Justyna Wojcik; Aleksandra Obuchowska; Alicja Ozga; Arkadiusz Standyło; Karolina Obuchowska; Żaneta Kimber-Trojnar; Bożena Leszczyńska-Gorzelak (Kazimierz Wielki University, 2020)
Introduction: The intestinal microflora (IM) is a heterogeneous complex of all microorganisms inhabiting the human body, both commensal, symbiotic and pathogenic. It consists mainly of bacteria, but also of viruses, archaea, fungi and protozoa. IM has an important metabolic and immunological role and participates in the course of pathological processes. The composition of a newborn and baby's IM changes dynamically in the first year of life. Just in the first days of birth, the newborn is exposed to many different strains of bacteria, including Staphylococcus sp.  and Enterococcus sp. Aim: To purpose of systematic review was to collect and analyze material of effect of the mother's gut microbiota on the pregnancy and of the health of baby. Material and methods:  Review of the literature published in 2008-2020. Conclusion: The uterus environment was originally considered sterile and the newborn's intestines were to be colonized only during and after delivery. However, recent studies indicate that placenta and amniotic fluid are involved in microbiota colonization of fetal intestines during prenatal life. This means that the fetus has an initial stock of microorganisms before birth. In addition, a significant effect of maternal diet and probiotic supplementation during pregnancy on the composition of microorganisms found in the amniotic fluid has been demonstrated. There is also a relationship between microbiotic programming in the aspect of civilization diseases.          Summary: The education of women of reproductive age on the subject of proper nutrition and supplementation during pregnancy and the puerperium is extremely important. Undertaking pro-health activities will affect the child's future health and development.